Understanding The Complexities of Teaching Marginalized Groups And Promoting Inclusive Education in Masjid Terminal School: Teachers’ Perspective - Windiana, Wiwin; Ulpah, Mariam (UIII Press, 2024)
Behind the success of the government programs, various educational phenomena in Depok City must still be resolved, one of which is education for marginalized communities. “Marginalized people” is a more accurate description of the urban poor. Consequently, the paramount task for the government is to harness the potential of these underprivileged individuals through the promotion of inclusive education. The Masjid Terminal School (Master School) is one of the schools in Depok that provides inclusive education. A qualitative method with a case study approach is used in this study. Semi-structured interviews, classroom observations and post-observation interviews were conducted to collect the data. The findings of this study revealed that the challenges faced by students at Master School differ significantly from those encountered at other schools. Given that Master School is tailored for underprivileged students, economic hardships emerge as one of their most formidable obstacles. Nevertheless, students at Master School are afforded opportunities to enhance their capacities and skills while enrolled, as the school not only provides tuition-free lessons but also offers a variety of extracurricular activities open to all students. Furthermore, teachers and staff at Master School actively support students with a strong desire to pursue higher education, with many students having secured scholarships to study abroad.